A Literature Review : Digital Leadership Style Analysis - Ahmat Mu Arif; Andi Indriani Ibrahim; Syahbudin Adam; Nurrahman Afriansyah; Serli MT Ngole; Nurwahyuni S. Boimin; Safitra Ramadani H. Patolo; Nurjana Umar Dapu (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
The rapid advancement of digital technology compels every organiza tion to adapt in order to remain sustainable and is not merely about adopting new technologies but also about fundamental changes in work culture, leadership becomes a key determinant of transformation success. This collection of studies explores how effective leadership serves as the main driving force of digital change across various sectors, including education. The reviwed Studies aim to analyze the critical roles and strategies of leadership in promoting the success of digital transformation across different domains. Futhemore, thhis reviem seeks to identify thhe most suitable leadership models and strategic actions needed for organizations to resmain resilient, competitive, and innovatitive,and innovative in the era of technological disruption. Most of the studies employ qualitative descriptive approaches and literature reviews (including bibliometric analyses) to digital leadership, strategic leadership, change management, and innovative organization cultures. Overal, the findings indings indicate that transformational and strategic leadership play central roles in achieving successful digital transformation. Leaders in the digital era are expected to: Possess strong digital capabilities,including digital literacy, data drive decision-making, and virtual communication skills.Foster an innovative culture by creating collaborative, change-oriented, and results-driven work enviromens.Manage organizational change adaptively, enabling smooth transitions toward modern systems while minimizing resistance among members.In the education sector, digital leadership facilitates the intrgration of technology into learning processes and, scool administrations, leaders play a crucial role in enhancing transparency, accountability, and the efficiency of public services. Meanwile, in business and e-business sectors, visionary leadership becomes the key driver of particularly for smess undergoing digital transformation. Digital transformation is not merely a technological shift but also a transformation in mindset and arganizational behavior. Success in the digital era depends on leaders’ ability to adapt, innovate, and empower human resources to face emerging challenges and seize new opportubities.